2017
DOI: 10.1021/acsami.6b14701
|View full text |Cite
|
Sign up to set email alerts
|

Precise Side-Chain Engineering of Thienylenevinylene–Benzotriazole-Based Conjugated Polymers with Coplanar Backbone for Organic Field Effect Transistors and CMOS-like Inverters

Abstract: Two donor-acceptor (D-A) alternating conjugated polymers based on thienylenevinylene-benzotriazole (TV-BTz), PTV6B with a linear side chain and PTVEhB with a branched side chain, were synthesized and characterized for organic field effect transistors (OFETs) and complementary metal-oxide-semiconductor (CMOS)-like inverters. According to density functional theory (DFT), polymers based on TV-BTz exhibit a coplanar and rigid structure with no significant twists, which could cause to an increase in charge-carrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…The UV–Vis absorption spectra revealed that the polymer has an optical band gap of 1.69 eV as shown in Figure . The band gap is similar to the ≈1.71 eV gap of PTV6B as previously reported by our group, which is referred to compare with PCTV‐BTzF because they have the same backbone structure. As expected, the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of PCTV‐BTzF are found to have energy levels of −4.86 eV/−3.17 eV, similar to those (−4.90 eV/−3.19 eV) of nonfluorinated PTV6B.…”
Section: Physical and Optical Properties Of Ptv‐btzfsupporting
confidence: 82%
See 3 more Smart Citations
“…The UV–Vis absorption spectra revealed that the polymer has an optical band gap of 1.69 eV as shown in Figure . The band gap is similar to the ≈1.71 eV gap of PTV6B as previously reported by our group, which is referred to compare with PCTV‐BTzF because they have the same backbone structure. As expected, the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of PCTV‐BTzF are found to have energy levels of −4.86 eV/−3.17 eV, similar to those (−4.90 eV/−3.19 eV) of nonfluorinated PTV6B.…”
Section: Physical and Optical Properties Of Ptv‐btzfsupporting
confidence: 82%
“…Recent advances in π‐conjugated polymer semiconductors have provided considerable improvements for many future applications, such as field‐effect transistors (FETs), light‐emitting diodes, and solar cells in low‐cost, large‐area printed and flexible electronics . In particular, high performance of FETs, surpassing that of FETs using amorphous inorganic semiconductors has been realized through the rational design of the backbone structures and engineering of alkyl side chains in π‐conjugated polymer . Recent studies demonstrated that π‐conjugated polymers with rigid and planar backbone structures provided high charge‐carrier mobilities in FETs .…”
Section: Physical and Optical Properties Of Ptv‐btzfmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of the side chains can be complex. For instance, the pristine thin film of P122 , in which the linear chains are attached to the benzotriazole units, shows higher charge mobility than that of P123 , which entails branching chains on the benzotriazole units . Interestingly, after thermal annealing P123 shows better semiconducting property than P122 .…”
Section: Alkyl Chains With Different Structuresmentioning
confidence: 99%